2021
DOI: 10.1177/15593258211055026
|View full text |Cite
|
Sign up to set email alerts
|

Choline Chloride Mediates Salinity Tolerance in Cluster Bean (Cyamopsis tetragonoloba L.) by Improving Growth, Oxidative Defense, and Secondary Metabolism

Abstract: Choline chloride (CC) application enhanced the tolerance of cluster bean ( Cyamopsis tetragonoloba L.) against salinity stress. The aim of the study was to determine the protective role of CC on plant growth, photosynthesis, and biochemical indicators of oxidative stress. The seeds of BR-99 (tolerant) and BR-2017 (sensitive) were surface sterilized and sown in plastic pots containing river sandy soil. The design of the experiments was completely randomized with 4 replicates per treatment. Three weeks after ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 109 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Chitosan (Ch) is a carbohydrate derivative from chitin, and it seems that its foliar application enhances the protection of crops against fungal attacks and reduces disease severity (El Amerany et al, 2020). Choline is a water-soluble vitamin recognized as a growth regulator under multiple stress conditions by improving growth, oxidative defense, and secondary metabolism (Riaz et al, 2021). Also, salicylic acid (SA) is a plant hormone that has been described to play an essential role in the activation and regulation of multiple responses to biotic and abiotic stresses, and it has been revealed that spraying plants with SA solution is favorable for plant growth and helps to protect them against abiotic stresses (Maruri-López et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (Ch) is a carbohydrate derivative from chitin, and it seems that its foliar application enhances the protection of crops against fungal attacks and reduces disease severity (El Amerany et al, 2020). Choline is a water-soluble vitamin recognized as a growth regulator under multiple stress conditions by improving growth, oxidative defense, and secondary metabolism (Riaz et al, 2021). Also, salicylic acid (SA) is a plant hormone that has been described to play an essential role in the activation and regulation of multiple responses to biotic and abiotic stresses, and it has been revealed that spraying plants with SA solution is favorable for plant growth and helps to protect them against abiotic stresses (Maruri-López et al, 2019).…”
Section: Introductionmentioning
confidence: 99%